The Unconventional Role for Gastric Volume in the Response to Bariatric Surgery for Both Weight Loss and Glucose Lowering. Issue 6 (June 2020) - Evers, Simon S.; Lewis, Alfor G.; Tong, Cindy; Shao, Yikai; Alvarez, Rafael; Ridelman, Elika; Grant, Bethany; Seeley, Randy J.
Abstract : Objective: To study the relationship between the amount of surgery-induced gastric volume reduction and long-term weight loss and glucose tolerance. Background Data: Vertical sleeve gastrectomy (VSG) has recently surpassed gastric bypass to become the most popular surgical intervention to induce sustained weight loss. Besides inducing significant weight loss, VSG also improves glucose tolerance. Although no clear correlation has been observed between the size of the residual stomach and sustained weight loss, this begs the question whether less aggressive gastric volume reduction may provide sufficient efficacy when weight loss is not the major goal of the surgical intervention. Methods: A series of strategies to reduce gastric volume were developed and tested in Long Evans male rats, namely: VSG, Fundal (F)-Resection, Gastric Sleeve Plication (GSP), Fundal-Plication, and Fundal-Constrained. Results: All surgical interventions resulted in a reduction of gastric volume relative to sham, but none of the interventions were as effective as the VSG. Gastric volume was linearly correlated to increased gastric emptying rate as well as increased GLP-1 response. Overall, cumulative food intake was the strongest correlate to weight loss and was logarithmically related to gastric volume. Regression modeling revealed a nonlinear inverse relation between body weight reduction and gastric volume, confirming that VSG is the only effective long-term weight loss strategy among the experimental operations tested. Conclusions: The data suggest a minimum threshold volume of the residual stomach that is necessary to induce sustained weight loss. Although all gastric volume interventions increased the GLP-1 response, none of the interventions, except VSG, significantly improved glucose tolerance. In conclusion, if weight loss is the primary goal of surgical intervention, significant volume reduction is required, and this most likely requires excising gastric tissue. Abstract : Supplemental Digital Content is available in the text